Vivencias de los pacientes con tuberculosis pulmonar Hospital Chepen - Correa Quispe, Charito Consuelo (2016)
Analyzing the experiences of patients with pulmonary tuberculosis was the purpose of this qualitative research, with phenomenological approach. The stage was Chepén Hospital, where 10 participants were interviewed, the technique used was the open depth interview. Speeches obtained were classified into 11 units of meaning: My job is guilty of tuberculosis, I lost my job, sadness, discouragement and fear of death, isolation, support from family and friends, the nurse my support, tuberculosis change my life, Tuberculosis stigma, Faith in God, treatment is unpleasant, my family infected me. The findings reveal what being a patient with tuberculosis, what you feel, how you live your fears and fears about death, it is isolated, think of all that lost by this disease. The nurse became one of his biggest supporters like the family plays a vital role in the treatment and recovery of patients with pulmonary tuberculosis.